Neglected Fracture in Maxillofacial: Case Series - Khairiza, Rizka; Setyarto, Muhammad Rizqy (Jurnal Plastik Rekonstruksi, 2020)
Introduction: Neglected fracture is a condition of fracture that is not handled or mishandled, resulting in a state of delay in treatment, or a worse condition and even a disability. The technical difficulty was associated with a greater incidence of complications and often lead to a suboptimal result. A more precise understanding of maxillofacial fracture's demographic patterns will help healthcare providers manage maxillofacial injuries. Method: Twenty-nine patients with neglected maxillofacial fractures were registered in the Division of Plastic Reconstructive and Aesthetic Surgery, Dr. Kariadi Central-General Hospital Semarang, January 2015 to December 2018. The collected information included gender, age, etiology, and site of fracture. Some of the cases are presented. Result: Neglected fracture of maxillofacial occurred predominantly in young adults. The male population was more frequently affected (62%)—most patients with neglected maxillofacial fractures associated with MVA (84%). The Mandible was the most common site of the fracture, followed by ZMC.  Conclusion: The possibility of a fracture of Mandible and ZMC or adjacent bones should be considered in any facial trauma, especially related to MVA injury. Early and proper management will provide a better result.